Development of Augmented Reality-Based Media for Polyhedron Materials - Priwantoro, Soffi Widyanesti; Fahmi, Syariful; Bueraheng, Surairee (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
There are difficulties for students in understanding concepts and illustrating polyhedron. Furthermore, the lack of learning media and the absence of technology based-media that can illustrate the material is an urgent problem that needs to be solved. Furthermore, the lack of learning media and the absence of technology-based media that can illustrate the material is an urgent problem that needs to be solved. Therefore, we developed Augmented Reality (AR) based learning media as a tool to help students visualise the material. This study used the Research and Development (R&D) model with the involvement of secondary school students (29 eighth-grade students). Before being tested, the media was validated by subject material experts and media experts with a minimum rating of good. The implementation was carried out twice, in small and large classes. The media was considered feasible if the minimum rating from each subject material expert, media expert, and student response was good. The results of the study showed that the subject material expert gave a score of 4.54 with a very good category, while the media expert gave a score of 4.31 with a very good category, and student responses scored 4.12 with a good category. Thus, the Augmented Reality (AR)-based learning media can be used in the learning process and can be further researched for its effectiveness. The novelty of this study lies in the development of AR-based learning media specifically focused on flat-sided spatial structures. The developed media enables students to visualise spatial structures in three dimensions, interactively, and contextually, thereby overcoming the limitations of conventional static media.